Significant linkage of BMI to chromosome 10p in the U.K. population and evaluation of GAD2 as a positional candidate. - Groves, C; Zeggini, E; Walker, M; Hitman, G; Levy, J; O'Rahilly, S; Hattersley, A; McCarthy, M; Wiltshire, S (2006)
Obesity is a major health problem, and many family-based studies have suggested that it has a strong genetic basis. We performed a genome-wide quantitative trait linkage scan for loci influencing BMI in 573 pedigrees from the U.K. We identified genome-wide significant linkage (logarithm of odds = 3.74, between D10S208 and D10S196, genome-wide P=0.0186) on chromosome 10p. The size of our study population and the statistical significance of our findings provide substantial contributions to the body of evidence for a locus on chromosome 10p. We examined eight single nucleotide polymorphisms (SNPs) in GAD2, which maps to this linkage region, tagging the majority of variation in the gene, and observed marginally significant (0.01